Functions of interjections in the modern English language - Vesselskaya, K.V. (KAZGUU Liberal Arts Digest Volume 1. M. NARIKBAYEV KAZGUU UNIVERSITY SCHOOL OF LIBERAL ARTS, 2021)
The Interjections of Modern English are a unique part of everyday speech, firstly, because of their little-studied nature and secondly, due to their rather interesting features, which altogether makes this topic actual for research. The purpose of the inquiry is to determine the most appropriate views of this specific part of speech; provide an overview of current relevant theories, including various classifications and distinctive features of their usage; set own original view on the concept and role of interjections and finally, elicit the functions interjections perform in the Modern English language. To investigate the central phenomena, the research utilized a qualitative method with some minor elements of a quantitative design. The paper presents two parts. The first is a theoretical one, which summarizes the most popular opinions of Western and some Russian linguists regarding the concept of interjection. The second part is a practical one, which distinguishes the functions of interjections in the Modern English through the analysis of the book of J. K. Rowling “Harry Potter and the Philosopher’s Stone” (1997) based on the semantic classification of Ameka (1992), presented in the theoretical part. Thanks to the both theoretical and practical approaches, a sufficient number of functions revealed: communicative, imperative, expressive and many others. The received data might be used by instructors for students majoring in Applied Linguistics and Translation Studies. Based on these findings the original functional dictionary of Modern English Interjections might be also developed. The draft version fragment of such an innovative dictionary is presented in the appendix
Keywords: Modern English, functions, interjections, literature analysis, functional dictionary